Pengaruh Kualitas Sistem Dan Kualitas Informasi Siakad Terhadap Kepuasan Pengguna Di Universitas Esa Unggul Tangerang - Gusti Muhamad Sardana; Bartholomeus Dimanche Carl Beth; Vinsens Aji Pamungkas; Taufik Maulana; Muhammad Adi Zacky Zahran; Riya Widayanti (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
This research aims to evaluate the impact of SIAKAD system and information quality on user satisfaction at Esa Unggul University, Tangerang. In this digital era, higher education institutions need to optimize information technology to support academic activities. Esa Unggul University has implemented SIAKAD for various academic purposes, including online registration, taking KRS, KHS, and accessing grades. However, there are still challenges such as slow access and inaccurate information. This research applies the SUS (System Usability Scale) method to measure system usability. A quantitative approach was used by conducting a survey of student users of SIAKAD. The findings show that system quality, especially the ease of use aspect, as well as information quality, especially accuracy, have a significant influence on user satisfaction. The level of user satisfaction is reflected in the high average score and positive perceptions of students regarding the effectiveness and efficiency of SIAKAD. However, there is still room for improvement, especially in the user interface and adding features that better support academic activities. The results of this research have important implications for Esa Unggul University in its efforts to improve the quality of SIAKAD to provide more optimal services to students.